PERTUMBUHAN DAN PEMANFAATAN HARTA (At-Tanmiyyah al-Iqtishadiyyah al-Mutakammilah) - Nailul Rahmi (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Abstrak In Islam, anyone was property, individual or sosiety or states. All of the people was can to used and develop they property based the Islamic low. Property in Islam is used whith by socialist value for society. Property in Islami must be used base Islamic low, as zakat, infaq, and sadaqah. All of people was property must be to do for develops they property, because its important to used for their life. Properti must be used to produktif development and can not used to deposited to disturb stability and sirkulation of economy in society. Kata Kunci : Pertumbuhan, pemanfaatan, harta